A review on thermophysical properties of nanoparticle dispersed phase change materials - Kibria, M.A.; Anisur, M.R.; Mahfuz, M.H.; Saidur, Rahman; Metselaar, I.H.S.C. (Elsevier, 2015)
A review of current experimental studies on variations in thermophysical properties of phase change material (PCM) due to dispersion of nanoparticles is presented in this article. Dispersed carbon nanotubes/fiber and different metal/metal oxide nano particles in paraffin and fatty acids might be a solution to improve latent heat thermal storage performance. Thermophysical properties such as thermal conductivity, latent heat, viscosity and super cooling of phase change materials (PCM) could be changed for different physical properties of dispersed nanoparticle such as size, shape, concentration and surface properties. Among the nano particles, comparatively carbon nanotubes and carbon nano fiber have shown better performance in enhancing the thermal properties of PCM for their unique properties. The present review will focus on the studies that describe how the surface, chemical and physical properties of nanoparticle could affect the thermal properties of PCM with the help of available explanations in the literature. (C) 2015 Elsevier Ltd. All rights reserved.